For every law, a loophole: Flexibility in the menu of Spanish business forms, 1886 - 1936 - Timothy W. Guinnane; Susana Martίnez Rodrίguez (Yale University, Economic Growth Center, 2012)
The Spanish business code allowed firms great flexibility in their organizational form in the late nineteenth and early twentieth century. Until 1920, firms had the same basic choices as in France and some other European countries, namely, the corporation, the ordinary partnership, or the limited partnership. But Spanish law was unusually flexible, allowing firms to adapt the corporation especially to the needs of its owners. Starting in 1920 Spanish firms could also organize as a Sociedad de Responsabilidad Limitada (SRL), a form similar to the German GmbH or the British Private Limited Company (PLC). But some firms had already adopted the form prior to 1920. The Spanish coded lacked the principle of numerus clauses that is central to many areas of law. Most business codes allow firms to choose only from a proscribed menu of options. The Spanish code offered these options but also stated that firms could organize in other ways if they wished. This paper uses three empirical sources to study the way firms actually used those possibilities. We find that this flexibility did not make entrepreneurs indifferent across the different organizational forms.
Keywords: K20; N43; N44; 330; spanish economic history; legal form of enterprise; law and finance